Mathematics Teachers' Performance in the Industrial Revolution Era 4.0: A Structural Equation Model - Dedek Andrian; Astri Wahyuni; Syarul Ramadhan (Yayasan Keluarga Guru Mandiri, 2022)
This research aimed to find the structural equation model of mathematics teachers' Performance in the Industrial Revolution 4.0 that fits according to data in the field. The Research population was secondary mathematics teachers of Riau Province, Indonesia. Research samples were a part of teachers who were taken based on the purposive sampling. The instrument was a questionnaire developed and validated through content and construct validity. Data analysis was a correlational technique with a structural equation modeling approach. The analysis result showed that the structural model arranged based on the literature study and expert FDG fit statistically. Five variables significantly affected the mathematics teachers’ performance in the industrial revolution 4.0 variables that is; Leadership, work motivation, teachers' self-efficacy, teachers' Creativity, and organizational climate. TPACK did not affect the industrial revolution 4.0. Leadership significantly affected Teachers' Self-Efficacy, Teachers' Creativity, Work motivation, TPACK, and organizational climate. The organizational climate significantly affected work motivation, TPACK, Teachers' Self-Efficacy, and Teachers' Creativity. Work Motivation significantly affected Teachers' Self-Efficacy, Teachers' Creativity, and TPACK. Teachers' Self-Efficacy did not affect Teachers' Creativity and TPACK. Teachers' Creativity significantly affected TPACK. Of 15 paths from endogenous to endogenous variables, 13 paths are significant, and two paths are not significant.